(untitled) (Journal of actual problems of jurisprudence, 2016)
In this article the main stages of development of a foreign viktimologiya are considered. The main directions of development the viktimologicheskikh of researches abroad are analyzed. In detail specialized programs of rehabilitation and service of the help to victims of crimes reveal. And also the attention to practice foreign the viktimologicheskikh of researches for receiving a solid data about crime and victims of crimes is paid.